A new view of treatment for ovarian cancer - S. V. Khokhlova (ABV-press, 2014)
The basic investigations in the past year are dedicated to search for new markers for the screening and early diagnosis of ovarian can- cer, to the definition of a role of retroperitoneal lymph dissection, the time of initiation of second-line treatment in the marker progres- sion of this disease, to the development of different modified regimens in both first-line therapy and recurrent ovarian cancer.